Effects of Bacillus safensis inoculation and p fertilizer on the growth of palm seedlings / Nurul Atiqah Zulkifli - Zulkifli, Nurul Atiqah (Faculty of Plantation and Agrotechnology, 2016)
Bacillus safensis is one of phosphate solubalizing bacteria (PSB) that act as plant regulator in plant. Bacteria that abundant in the soil forces recycling the soil nutrient that crucial for soil fertility, induced better rooting development and improving crop production. There are many beneficial effects of PSB on plants that have been described but the use of PSB as bio-fertilizer in oil palm seedlings is less documented. The ability of Bacillus safensis to improve growth of oil palm seedlings and the effects on P availability in presence of Chritsmas island rock phosphate (ClRP) were carried out in the pot experiment at the Greenhouse, UiTM Jasin. The experiment was arranged in Completely Randomized Design(CRD) with four treatment and three replication . Treatments include seeds that inoculated with Bacillus safensis and presence of ClRP (P-PSB), seeds that not inoculated with Bacillus safensis and presence of CIRP (PWPSB), seeds that inoculated with Bacillus safensis and absence of CIRP (PSB) and control treatment , seeds that not inoculated with Bacillus safensis and absence of CIRP (WPSB). Sterilized seed of oil palm seedlings were planted in polybag containing 1kg soil and the growth performance of the treatment observed for four weeks of germination. The treated seed with Bacillus safensis significantly increased the height of seedlings (38.18 em) and improved the roots development compare to non- inoculated treatments. The presence of CIRP in the soil solution increased the P uptake in plants and result in positive effect on seedling growth in respect to average of root length, shoot length, height of seedlings, number of roots and number of leaves. The results showed that inoculation of oil palm seedlings with Bacillus safensis improve phosphate solubilizing activity of incorporated CIRP. The inoculation could improved the growth development of host plant and hence be used as microbial fertilizer in minimized the dependence on chemical fertilizer and providing a sustainable agriculture.